2008
DOI: 10.1124/dmd.108.021964
|View full text |Cite
|
Sign up to set email alerts
|

Role of EnzymaticN-Hydroxylation and Reduction in Flutamide Metabolite-Induced Liver Toxicity

Abstract: ABSTRACT:Flutamide is used for prostate cancer therapy but occasionally induces severe liver injury. Flutamide is hydrolyzed in the body into 5-amino-2-nitrobenzotrifluoride (FLU-1) and then further oxidized. In our previous study, N-hydroxy FLU-1 (FLU-1 N-OH) was detected in the urine of patients and exhibited cytotoxicity in rat primary hepatocytes. In the present study, we have assessed the roles of FLU-1 N-oxidation and hepatic glutathione (GSH) depletion in liver injury. FLU-1 (200 mg/kg p.o.) was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Several studies suggested that the flutamide-induced hepatotoxicity was caused by FLU-1, a metabolite of hydrolyzed flutamide, or N-hydroxyl FLU-1, a metabolite of FLU-1 by CYP3A or CYP1A (Aizawa et al, 2003;Matsuzaki et al, 2006;Ohbuchi et al, 2009). Therefore, it was considered that flutamide hydrolysis was important in the occurrence of hepatotoxicity, but the flutamide hydrolase enzyme had never been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested that the flutamide-induced hepatotoxicity was caused by FLU-1, a metabolite of hydrolyzed flutamide, or N-hydroxyl FLU-1, a metabolite of FLU-1 by CYP3A or CYP1A (Aizawa et al, 2003;Matsuzaki et al, 2006;Ohbuchi et al, 2009). Therefore, it was considered that flutamide hydrolysis was important in the occurrence of hepatotoxicity, but the flutamide hydrolase enzyme had never been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study on patients of prostate cancer taking flutamide showed that the incidence of hepatotoxicity was correlated with the plasma concentration of FLU-1 (Aizawa et al, 2003). More recently, Ohbuchi et al (2009) reported that coadministration of FLU-1 and 1,4-bis[2-(3,5-dichloropyridyloxy)]benzene, an inducer of CYP3A and CYP1A, to mice significantly increased serum alanine aminotransferase, and sev-eral protein adducts were detected after incubation of the microsomal protein with N-hydroxy FLU-1. Therefore, the hepatotoxicity of flutamide might be related to N-hydroxy FLU-1.…”
mentioning
confidence: 99%
“…Thus, there may be inter-or intraindividual variations in CES2 expression and function that affect the flutamide pharmacokinetics. The flutamide-hydrolyzed metabolite, FLU-1, is further metabolized to N-hydroxy FLU-1 by human CYP3A4, and N-hydroxy FLU-1 is thought to be associated with hepatotoxicity (Ohbuchi et al, 2009). Further study is needed to clarify the association of CES2 and AADAC with flutamide-induced hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that 2-hydroxyflutamide is associated with the therapeutic effect of flutamide (Katchen and Buxbaum, 1975), whereas FLU-1 is considered to have no therapeutic effect (Aizawa et al, 2003). FLU-1 is further metabolized to N-hydroxy FLU-1 by human CYP3A4, and N-hydroxy FLU-1 is considered to be associated with hepatotoxicity (Ohbuchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Flutamide induced severe hepatic dysfunction. Ohbuchi et al (2008) suggested that CYP3A4 catalyzed the N-oxidation of the amino metabolite of flutamide, which had hepatotoxic effects. Although the bioactivation pathways of nitrobenzodiazepines still remain unclear, they may undergo metabolic activation similar to that of other drugs.…”
Section: Metabolic Activation Of Nitrobenzodiazepinesmentioning
confidence: 99%